Are Tourists Motivated by Dark Experiences Beyond Leisure and Cultural Learning? The Case of the Walled City of the Philippines - Caculitan Encio, Valvince; Empeño, Collin; Totin Cleofe, Ryndelle (International Journal of Sustainable Competitiveness on Tourism, 2026)
This study examines the main motivations of tourists visiting Intramuros as a dark tourism destination and identifies the factors influencing their travel decisions. Specifically, it seeks to determine what motivates visitors to explore the historical and tragic aspects of Intramuros. The study used a quantitative research design conducted in Intramuros, Manila. Respondents were selected tourists visiting the site, and data were collected through structured survey questionnaires. Statistical treatments such as frequency distribution, percentage, and mean scores were applied to analyze the data. Findings reveal that tourists are highly motivated by the desire to learn about history, particularly stories of war, colonialism, and national heroes. Emotional connection, curiosity about tragic events, and cultural appreciation were identified as the top motivating factors influencing visitation. The results show that Intramuros remains appealing because of its preserved historical structures combined with meaningful dark historical narratives. Overall, historical interest and educational value emerged as the strongest motivational drivers among visitors. The study highlights the importance of strengthening historical interpretation and  storytelling to enhance visitor experience. Understanding tourism motivation in dark tourism destinations can help improve management strategies and promote sustainable cultural tourism development.